The effect of three hand disinfectants on Staphylococcus aureus resistant to methicillin in different periods of time - Zohreh Moradi; Masumeh Hasani Tabatabaei; Abolfazl Fateh; Mohammad Javad Torkamani; Ladan Ranjbar Omrani; Sara Valizadeh (Tehran University of Medical Sciences, 2019)
Background and Aims: Methicillin-resistant Staphylococcus Aureus (MRSA) is an important infection source in dentistry for different disinfectants to be used to prevent its transmission. Furthermore, a variety of chemical disinfectants are developed to remove bacterial infections from the dental care workers' hands and claims are made regarding their superiority in infection control, although all requires scientific investigations. The aim of present study was to compare the effects of chemical hand-disinfectants Micro Zed HD, Aseptoman and Decosept on MRSA (methicillin resistant staphylococcus aureus) in different periods of time. Materials and Methods: In this experimental study, the antibacterial efficacy of three hand-disinfectants on standard strain of MRSA (USA300: ATCC® BAA-1717™) was evaluated according to European standard of evaluating antiseptics (EN 1040:2005 CSN EN). First we prepared a 0.5 Mc Farland (108 CFU/ml) suspension of MRSA, and exposed to three disinfectants for 15, 30, 60 and 90 seconds. Then, they were transferred to separate plates of Mueller-Hinton medium and incubated in 37◦C for 24 hours. The plates were compared then with control plate to evaluate the efficacy of materials on bacteria by calculating the CFU/ml of plates. Results: Three hand-disinfectants evaluated in this study had the maximum anticabterial effect on MRSA in the minimum time of exposure (15 seconds), and we found no trace of growth in any plates. Conclusion: The three hand-disinfectans (MicroZed HD, Aseptoman and Decosept) in the concentration suggested by their companies, showed no difference in efficacy to remove MRSA from hands.